Probing the Phosphopeptide Specificities of Protein Tyrosine Phosphatases, SH2 and PTB Domains with Combinatorial Library Methods - Vetter, S.W.; Zhang, Z-Y. (Current Protein and Peptide Science, 2002)
Protein tyrosine phosphatases, SH2 and PTB domains are crucial elements for cellular signal transduction and regulation. Much effort has been directed towards elucidating their specificity in the past decade using a variety of approaches. Combinatorial library methods have contributed significantly to the understanding of substrate and ligand specificity of phosphoprotein recognizing domains.This review gives a brief overview of the structural characteristics of protein tyrosine phosphatases, SH2 and PTB domains and their binding to phosphopeptides. The chemical synthesis of peptides containing phosphotyrosine or phosphotyrosine mimics and the various formats of synthesis and deconvolution of combinatorial libraries are explained in detail. Examples are given as how different combinatorial libraries have been used to study the interaction of phosphopeptides with SH2 domains and phosphatases. The intrinsic advantages and difficulties of library synthesis, screening and deconvolution are pointed out. Finally, some experimental results on the substrate specificity of protein tyrosine phosphatase 1B and the SH2 domain of the adaptor protein Grb-2 are summarized and discussed.
Keywords: Phosphopeptide Specificities